License Auctions with Royalty Contracts for Losers - Thomas Giebe; Elmar G. Wolfstetter (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
This paper revisits the standard analysis of licensing a cost reducing innovation by an outside innovator to a Cournot oligopoly. We propose a new mechanism that combines elements of a license auction with royalty licensing by granting the losers of the auction the option to sign a royalty contract. The optimal new mechanism eliminates the losses from exclusionary licensing without reducing bidders' surplus; therefore, it is more profitable than both standard license auctions and pure royalty licensing. We also take into account that the number of licenses must be an integer, which is typically ignored in the literature.
urn:nbn:de:bvb:19-epub-13455-6
Keywords: D21; D43; D44; D45; 330; Patents; Licensing; Auctions; Royalty; Innovation; R&D; Mechanism Design